Sirenomelia: A case of severe caudal regression syndrome - (:unkn) unknown (My University, 2004)
Nadir olarak görülen;birleşik alt ekstremiteler, fibula yokluğu, bilateral renal agenezi ve geniş tek umbilikal arter ile karakterize ağır kaudal regresyon sendromu tanımlanmıştır. Yaşam şansı çok nadir olup yalnız bilateral renal agenezi yokluğunda mümkündür. Utrasonografi ile erken tanının ve ardından daha az travmatik terminas-yonun önemi tartışılmıştır.

A rare case of severe caudal regression syndrome including fused lower limbs, absence of fibula, anal atresia, bilateral renal agenesis, and a single large umbilical artery is described. Survival is extremely rare in such cases and only possible in the absence of bilateral renal agenesis.The importance of early diagnosis by ultrasonography and subsequently less travmatic termination are discussed.
Sirenomelia: Ağır kaudal regresyon sendromlu bir olgu
Keywords: Cerrahi